2018
DOI: 10.1016/j.aju.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of flank hernias and bulges following surgical flank approaches to the kidney in adults

Abstract: ObjectivesTo evaluate the incidence and risk factors for the development of flank incisional hernias or bulges following surgical flank approaches to the kidney.Patients and methodsIn all, 100 consecutive adult patients who underwent variable renal surgeries via flank approaches were included in this prospective study. The incidence and risk factors for flank hernias and bulges were studied at 1- and 6-months postoperatively.ResultsAt 6 months postoperatively, the incidence of flank bulge was 14% and for lumba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…Lower incidence of postoperative abdomen bulge or incisional hernia: In addition to the commonly recognized factors such as incision infection, old age, and high BMI, many studies have shown that the injury of muscle and neurovascular bundle (NVB) were significant risk factors for the occurrence of postoperative abdomen bulge or incisional hernia. 18,19 Some studies have also reported that increased incision length, prolonged operation time and long-term using of retractors during surgery were statistically significant factors in the development of incisional hernia. 20,21 In the present study, the incidence of postoperative abdomen bulge or incisional hernia in the CRT group was less than that in the standard group, the reasons may be related to the above factors.…”
Section: Discussionmentioning
confidence: 99%
“…Lower incidence of postoperative abdomen bulge or incisional hernia: In addition to the commonly recognized factors such as incision infection, old age, and high BMI, many studies have shown that the injury of muscle and neurovascular bundle (NVB) were significant risk factors for the occurrence of postoperative abdomen bulge or incisional hernia. 18,19 Some studies have also reported that increased incision length, prolonged operation time and long-term using of retractors during surgery were statistically significant factors in the development of incisional hernia. 20,21 In the present study, the incidence of postoperative abdomen bulge or incisional hernia in the CRT group was less than that in the standard group, the reasons may be related to the above factors.…”
Section: Discussionmentioning
confidence: 99%
“…Lower incidence of postoperative abdomen bulge or incisional hernia. In addition to the commonly recognized factors such as incision infection, old age, and high BMI, many studies have shown that the injury of muscle and neurovascular bundle (NVB) were significant risk factors for the occurrence of postoperative abdomen bulge or incisional hernia [10,11]. Some studies have also reported that increased incision length, prolonged operation time and long-term using of retractors during surgery were statistically significant factors in the development of incisional hernia [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Our current understanding of the pathogenesis of postoperative flank bulges focusses on nerve injury that leads to postoperative muscle paresis, denervation, and muscle atrophy [6,8]. Indeed, retrospective studies reported a reduced muscle volume after open partial nephrectomy, as well as a significant number of patients suffering from paraesthesia and numbness of the abdominal wall [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is controversy relating to the precise rates of these complications, the incidence of flank bulge formation has been reported to occur in up to 57% of patients after open flank incision [4,5]. Moreover, incisional hernia following flank incision has been described in up to 17% of patients [6].…”
Section: Introductionmentioning
confidence: 99%